A graphical tool for analysis and design of bi-characteristic-impedance transmission lines - Torrungrueng, D.; Chou, P. Y.; Krairiksh, M. (My University, 2007)
The bi-characteristic-impedance transmission lines (BCITLs) are generally lossy transmission lines that possess different complex characteristic impedances for waves propagating in forward and reverse directions. Because of complicated equations associated with BCITLs, a graphical tool is necessary in the analysis and design. In this article, the standard T-chart developed for conjugately characteristic-impedance transmission lines (CCITLs) is generalized to treat BCITL problems, called a generalized T-chart. It is found that the way of using this new graphical tool is similar to that of the standard T-chart. However, the magnitude of the voltage reflection coefficient associated with BCITLs may be greater than unity for some passive load terminations. An example of using a generalized T-chart is provided in this paper. © 2007 Wiley Periodicals, Inc.
Keywords: Bi-characteristic-impedance transmission lines (BCITLs); Conjugately characteristic-impedance transmission lines (CCITLs); Generalized T-chart; Standard T-chart